2013
DOI: 10.1127/1863-9135/2013/0328
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation by fragments in six common aquatic macrophyte species

Abstract: Vegetative reproduction is the most common form of propagation in aquatic macrophytes. Fragmentation and consecutive re-rooting of the fragments is one way in which new macrophyte colonies may establish. The success and frequency of this strategy depends on the species and the environment. This study tested how well six species are capable of colonising this way. Tested species are five of the most abundant species of Lake Balaton, where macrophyte recolonisation is still to take place after improving water qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
3
17
1
Order By: Relevance
“…The lower regeneration capacities were possible at least partly caused by the exclusion of fragments with apical buds from our experiment, which are known for their high regenerative capacity (Riis et al, 2009;Vari, 2013). As the present study was carried out during summer, it can be ruled out that seasonal effects played a role (Vari, 2013). The average regeneration time was 2-3 weeks in this study, which is similar to the rooting times reported for other submerged species (Vari, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The lower regeneration capacities were possible at least partly caused by the exclusion of fragments with apical buds from our experiment, which are known for their high regenerative capacity (Riis et al, 2009;Vari, 2013). As the present study was carried out during summer, it can be ruled out that seasonal effects played a role (Vari, 2013). The average regeneration time was 2-3 weeks in this study, which is similar to the rooting times reported for other submerged species (Vari, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…As the present study was carried out during summer, it can be ruled out that seasonal effects played a role (Vari, 2013). The average regeneration time was 2-3 weeks in this study, which is similar to the rooting times reported for other submerged species (Vari, 2013). Elodea canadensis and E. nuttallii showed the shortest regeneration time, which might influence the establishment rate of produced plant fragments.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The high frequency of asexual reproduction in aquatic plants, especially the wide occurrence of shoot fragments as a major way of dispersal (e.g. Vari, 2013), conceals the normally clear distinction between growth and reproduction in land plants.…”
Section: Asexual Reproduction: Increased Opportunity On Release From mentioning
confidence: 99%